Solidarity and Chance: Ethnographic Insights from an Italian Bingo Hall - Manzocchi, Marco; Galbignani, Beatrice; Lanfranchi, Sofia; Romito, Marco; Zanutto, Giorgio Michele (Critical Gambling Studies, 2026)
As in many other countries, bingo in Italy occupies a peculiar status: it exists in a gray area between the image of pathological gambling and a harmless pastime for the elderly. This marginal position within public gambling offers an opportunity to study the phenomenon beyond the pathological narrative. Through a team ethnography conducted in a bingo hall in Milan, we explored how practices of chance-taking intertwine with social dynamics of solidarity. Our observations reveal that engagement with chance—often through repeated losses—fosters a sense of shared fate among players, reinforced by collective superstitions and ritual behaviors that transform gaming tables into spaces of communal emotion. Individual wins become collective celebrations through ritualized redistribution of money, while losses are softened by mutual recognition and complaint. These practices create emotional bonds, particularly among marginalized groups. In this article, we interweave diary-like narrative reflections with theoretical analysis and contextualize our findings within Italy’s gambling regulatory framework. Our aim is to restore dignity to bingo players, emphasizing the hall not merely as a site of consumption, but also as a space where social ties and emotional solidarities emerge and are sustained.